(untitled) (Research, Society and Development, 2023)
The COVID-19 pandemic changed the health system so that priority was given to patients suspected or infected by the coronavirus, influencing the discontinuation of screening procedures such as cytopathological examination of the uterine cervix. The study aimed to identify the impact of the COVID-19 pandemic on cervical cancer (CC) screening in the state of Pará, Brazil. This is a descriptive research, correlating data recorded at the Department of Informatics of the Unified Health System (DATASUS). In this sense, the number of cytopathological examinations of the uterine cervix performed between March 2019 and February 2020 (pre-pandemic) and from March 2020 to February 2021 (pandemic) was analyzed. From this, the number of tests performed was correlated with the number of cases of COVID-19 registered in the state of Pará between March 2020 and February 2021, on the monitoring website of the public health department of the state of Pará. It was observed that there was a significant decrease in the number of screening tests performed during the pandemic, 45% compared to the pre-pandemic period, as well as a negative correlation between the pandemic and the performance of the screening test. Thus, the pandemic had a negative impact on screening for cervical cancer, which can lead to late diagnosis and treatment, thus necessitating the promotion of strategies to increase screening coverage for CC in primary care.